Screening tool for malignant bowel obstruction in relapsed, metastatic ovarian cancer. Issue 2 (21st March 2019) - Morgan, Robert D; Stamatopoulou, Sofia; Mescallado, Nerissa; Saunders, Geoff; Welch, Richard; Mitchell, Claire; Hasan, Jurjees; Clamp, Andrew R; Jayson, Gordon C
Abstract : Background: Malignant bowel obstruction (MBO) is a common cause of morbidity and mortality in women diagnosed with ovarian cancer. Earlier detection of MBO may improve patient outcomes. There are currently no screening tools to assist detection. Aim: We report a screening questionnaire that can be used to detect MBO, and how the severity score for key clinical symptoms correlate with radiological evidence of MBO from ovarian cancer. Design: A case–control study in which patients with relapsed, metastatic ovarian cancer were asked to answer 10 questions related to key clinical symptoms associated with intestinal obstruction. The study group included women with CT-confirmed MBO, whereas the control group had no evidence of MBO. Patients scored each question according to severity from 1 (least severe) to 5 (most severe). Setting/participants: Between 1 June and 31 December 2016, 37 women completed the screening questionnaire. Results: Patients in the study group (n=17) reported significantly higher (ie, more severe) scores for abdominal pain, nausea, vomiting and constipation. In contrast, differences in severity scores between groups did not differ significantly in response to questions regarding abdominal swelling, borborygmi, diarrhoea or loss of appetite. All patients in the study group more frequently stated that their symptoms had deteriorated within the 2 months prior to completing the questionnaire. Conclusion: Here we report the key clinical symptoms associated with radiologically-confirmed MBO in relapsed, metastatic ovarian cancer. We recommend healthcare practitioners focus on these specific symptoms during patient consultations in order to improve risk stratification of MBO.